Optical laminate and image display device
Patent Information
- Application Number
- JP2024126001
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-30
- Filing Date
- 2024-08-01
- Publication Date
- 2025-03-14
AI Technical Summary
【0007】 本発明によれば、熱による対基板密着力の上昇を緩やかにでき、リワーク性を向上させることができる光学積層体、及びそれを用いた画像表示装置を提供することができる。
Smart Images

Figure 2025036152000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical laminate and an image display device. [Background technology]
[0002] Polarizing plates are widely used in image display devices. Examples of image display devices include liquid crystal display devices and organic EL display devices. Polarizing plates are distributed in a state where a transparent protective film is laminated on both sides or one side of a polarizer, an adhesive layer is formed on at least one surface, and a release film is attached to the adhesive layer. In addition, a phase shifter is laminated on a polarizing plate in a state where a protective film is attached to both sides or one side of a polarizer to form a composite polarizing plate, and an adhesive layer is formed on the phase shifter side. Before being attached to an image display device, the release film is peeled off from the adhesive layer on the surface of these polarizing plates, composite polarizing plates, and phase shifters, and the exposed adhesive layer is attached to a substrate such as glass of the image display device. An optical laminate having such an adhesive layer is disclosed in, for example, Patent Document 1. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 6-313807 Summary of the Invention [Problem to be solved by the invention]
[0004] An optical laminate having a pressure-sensitive adhesive layer is required to be easily peeled off from the substrate of an image display device as necessary, i.e., to have good reworkability. However, in conventional optical laminates, the adhesive strength of the pressure-sensitive adhesive layer to the substrate is easily increased by heat in a short period of time (for example, within 24 hours), and reworkability is not necessarily sufficient.
[0005] Therefore, an object of the present invention is to provide an optical laminate capable of slowing down an increase in adhesion to a substrate due to heat and improving reworkability, and an image display device using the same. [Means for solving the problem]
[0006] In order to solve the above problems, the present invention provides the following optical laminate and image display device. [1] An optical laminate having a resin film, a coating layer, and a pressure-sensitive adhesive layer in this order, the coating layer containing carbon nanotubes, and the pressure-sensitive adhesive layer containing a (meth)acrylic resin (A), a crosslinking agent (B), a silane compound (C), and an antistatic agent (D). [2] The optical layered body according to the above [1], wherein the antistatic agent (D) is an ionic compound comprising a nitrogen-containing organic cation and an anion. [3] The optical layered body according to the above [2], wherein the nitrogen atom-containing organic cation is a cation represented by the following formula (I): [ka] [In formula (I), R 5 , R 6 , R 7 and R 8 each independently represents a hydrogen atom, an optionally substituted alkyl group, an optionally substituted alkenyl group, an optionally substituted alkynyl group, an optionally substituted aryl group, or an optionally substituted heterocyclic group; R 5 , R 6 , R 7 and R 8 Adjacent substituents may be bonded together to form a ring.] [4] The optical laminate according to the above [2] or [3], wherein the anion is a fluorine atom-containing anion. [5] The optical layered body according to the above [4], wherein the fluorine atom-containing anion is an anion represented by the following formula (II): [Y(SO 2 C q F 2q+1 )p ] - (II) [In formula (II), Y represents a carbon atom or a nitrogen atom, and when Y is a carbon atom, p is 3, and when Y is a nitrogen atom, p is 2, and q represents an integer of 0 to 10.] [6] The optical laminate according to the above [2] or [3], wherein the anion is at least one selected from the group consisting of a p-toluenesulfonate anion, a dimethylphosphinate anion, a thiocyanate anion, a carbonate anion, a tetraarylborate anion, and a dicyanamide anion. [7] The optical layered body according to any one of the above [1] to [6], which has a hard coat layer between the resin film and the coating layer. [8] The optical laminate according to any one of the above [1] to [7], which has a polarizer on the opposite side of the resin film to the coating layer. [9] The optical laminate according to [8] above, further comprising a second resin film on the opposite side of the polarizer to the resin film.
[10] An image display device comprising the optical laminate according to any one of the above [1] to [9]. Effect of the Invention
[0007] According to the present invention, it is possible to provide an optical laminate capable of slowing down an increase in adhesion to a substrate due to heat and improving reworkability, and an image display device using the same. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of an optical laminate according to the present invention. [Diagram 2] 1 is a GPC chromatogram showing the high molecular weight region and the low molecular weight region of a (meth)acrylic resin (A). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings where necessary. [Optical laminate] The optical laminate of the present invention has a resin film, a coating layer, and a pressure-sensitive adhesive layer in this order, the coating layer contains carbon nanotubes, and the pressure-sensitive adhesive layer contains a (meth)acrylic resin (A), a crosslinking agent (B), a silane compound (C), and an antistatic agent (D). According to the optical laminate, the coating layer contains carbon nanotubes, and the pressure-sensitive adhesive layer contains the specific component, so that the increase in adhesion to the substrate due to heat can be made gentle, and reworkability can be improved. Although the reason for such an effect is not necessarily clear, the present inventors speculate that the inclusion of carbon nanotubes in the coating layer makes it easier for the antistatic agent in the pressure-sensitive adhesive layer to segregate on the surface of the pressure-sensitive adhesive layer opposite to the coating layer, and the presence of this segregated antistatic agent can make it possible to make the increase in adhesion between the laminated substrate and the pressure-sensitive adhesive layer due to heat gentle.
[0010] FIG. 1 shows a schematic cross-sectional view of an optical laminate according to one embodiment of the present invention. The optical laminate 100 shown in FIG. 1 has a pressure-sensitive adhesive layer 1, a coating layer 2, a hard coating layer 3, a first resin film 4, a retardation layer 5, a first bonding layer 6, a polarizer 7, a second bonding layer 8, and a second resin film 9 in this order. The polarizer 7 is protected by a first protective layer 10 made of a hard coating layer 3, a first resin film 4, and a retardation layer 5, which is bonded to one surface of the polarizer 7 via the first bonding layer 6, and a second protective layer made of a second resin film 9, which is bonded to the surface of the polarizer 7 opposite to the first protective layer 10 via the second bonding layer 8. The polarizer 7, the first and second bonding layers 6, 8, and the first and second protective layers 10, 9 form a polarizing plate 20. A separate film may be provided on the surface of the pressure-sensitive adhesive layer 1 opposite to the coating layer 2. Each layer constituting the optical laminate 100 will be described below.
[0011] <Adhesive layer 1> The pressure-sensitive adhesive layer contains a (meth)acrylic resin (A), a crosslinking agent (B), a silane compound (C), and an antistatic agent (D). The pressure-sensitive adhesive layer can be formed using a pressure-sensitive adhesive composition containing each of the above components. Each component constituting the pressure-sensitive adhesive layer will be described below.
[0012] (1) (Meth)acrylic resin (A) The (meth)acrylic resin (A) may contain a structural unit derived from an alkyl (meth)acrylate (a) (hereinafter also referred to as "alkyl (meth)acrylate (a)") having a homopolymer glass transition temperature (hereinafter also referred to as "Tg") of less than 0°C, a structural unit derived from an alkyl (meth)acrylate (b) (hereinafter also referred to as "alkyl (meth)acrylate (b)") having a homopolymer glass transition temperature of 0°C or higher, and a structural unit derived from a monomer (c) having a polar group. In this specification, (meth)acrylic means that it may be either acrylic or methacrylic. (Meth)acrylate means that it may be either acrylate or methacrylate.
[0013] As the Tg of the homopolymer of the alkyl (meth)acrylates (a) and (b), values given in literature such as POLYMER HANDBOOK (Wiley-Interscience) can be used.
[0014] Specific examples of the alkyl (meth)acrylate (a) include linear or branched alkyl acrylates having an alkyl group carbon number of 2 to 12, such as ethyl acrylate, n- and i-propyl acrylate, n- and i-butyl acrylate, n-pentyl acrylate, n- and i-hexyl acrylate, n-heptyl acrylate, n- and i-octyl acrylate, 2-ethylhexyl acrylate, n- and i-nonyl acrylate, n- and i-decyl acrylate, and n-dodecyl acrylate; linear or branched alkyl methacrylates having an alkyl group carbon number of 4 to 12, such as n-pentyl methacrylate, n- and i-hexyl methacrylate, n-heptyl methacrylate, n- and i-octyl methacrylate, 2-ethylhexyl methacrylate, n- and i-nonyl methacrylate, n-decyl methacrylate, and n-dodecyl methacrylate. The alkyl (meth)acrylate (a) may be an alkyl (meth)acrylate having an alicyclic structure (cycloalkyl (meth)acrylate), but from the viewpoint of conformity to the optical film (or flexibility or adhesion), it is preferably an alkyl acrylate having 2 to 10 carbon atoms, more preferably an alkyl acrylate having 3 to 8 carbon atoms, and even more preferably an alkyl acrylate having 4 to 6 carbon atoms. Only one type of alkyl (meth)acrylate (a) may be used alone, or two or more types may be used in combination.
[0015] From the viewpoint of mechanical strength and heat resistance durability, the content of the structural units derived from the alkyl (meth)acrylate (a) is preferably 40 parts by mass or more and 90 parts by mass or less, more preferably 45 parts by mass or more and 80 parts by mass or less, and even more preferably 50 parts by mass or more and 75 parts by mass or less, relative to 100 parts by mass of all the structural units constituting the (meth)acrylic resin (A).
[0016] Specific examples of the alkyl(meth)acrylate (b) include methyl acrylate, methyl methacrylate, stearyl acrylate, tert-butyl acrylate, ethyl methacrylate, isobutyl methacrylate, n-butyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, propyl methacrylate, and isopropyl methacrylate. The alkyl(meth)acrylate (b) may be an alkyl(meth)acrylate (cycloalkyl(meth)acrylate) having an alicyclic structure. The alicyclic structure may be a cycloparaffin structure having a carbon number of usually 5 or more, preferably about 5 to 7. Specific examples of alkyl (meth)acrylates having an alicyclic structure include isobornyl methacrylate, cyclohexyl methacrylate, dicyclopentanyl methacrylate, trimethylcyclohexyl methacrylate, tert-butylcyclohexyl methacrylate, 1-adamantyl methacrylate, isobornyl acrylate, cyclohexyl acrylate, dicyclopentanyl acrylate, cyclododecyl acrylate, methylcyclohexyl acrylate, trimethylcyclohexyl acrylate, tert-butylcyclohexyl acrylate, and α-ethoxy cyclohexyl acrylate. The alkyl (meth)acrylate (b) may be used alone or in combination of two or more. From the viewpoint of adjusting the glass transition temperature of the low molecular weight region component and the high molecular weight region component described later, it is preferable that the alkyl (meth)acrylate (b) is used in combination with an alkyl methacrylate and an alkyl acrylate.
[0017] From the viewpoint of mechanical strength and heat resistance durability, the content of the structural units derived from the alkyl (meth)acrylate (b) is preferably 1 part by mass or more and 40 parts by mass or less, more preferably 3 parts by mass or more and 30 parts by mass or less, and even more preferably 5 parts by mass or more and 20 parts by mass or less, relative to 100 parts by mass of all structural units constituting the (meth)acrylic resin (A).
[0018] The alkyl(meth)acrylate (a) and the alkyl(meth)acrylate (b) may be an alkyl(meth)acrylate in which a substituent has been introduced into the alkyl group in the alkyl(meth)acrylate (a hydrogen atom of the alkyl group has been substituted with a substituent). The substituent may be, for example, an aryl group (such as a phenyl group), an aryloxy group (such as a phenoxy group), or an alkoxy group (such as a methoxy group or an ethoxy group).
[0019] The monomer (c) having a polar group can be an ethylenically unsaturated monomer having one or more polar groups in the molecular chain. Examples of the monomer (c) having a polar group include a monomer having a hydroxyl group, a monomer having a carboxyl group, and a monomer having a nitrogen atom. The monomer (c) having a polar group may be used alone or in combination of two or more kinds.
[0020] From the viewpoint of mechanical strength and heat resistance durability, the content of the structural unit derived from the monomer (c) having a polar group is preferably 0.1 parts by mass or more and 10 parts by mass or less, more preferably 0.3 parts by mass or more and 5 parts by mass or less, and even more preferably 0.5 parts by mass or more and 3 parts by mass or less, relative to 100 parts by mass of all structural units constituting the (meth)acrylic resin (A).
[0021] Examples of the monomer having a hydroxy group include those represented by the following formula (1): [ka] [In formula (1), n represents an integer of 1 to 5; A 1 represents a hydrogen atom or an alkyl group, X 1 represents a methylene group which may have a substituent, and when n is 2 or more, the substituents may be the same or different. Examples of the hydroxyl group-containing (meth)acrylate include those represented by the following formula:
[0022] In formula (1), A1 Examples of the alkyl group that can constitute the above group include alkyl groups having 1 to 10 carbon atoms, such as a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a s-butyl group, a tert-butyl group, a pentyl group, and a hexyl group. Among these, a methyl group is preferred.
[0023] In formula (1), X 1 Examples of the substituent that the methylene group may have include halogen atoms (fluorine atoms, chlorine atoms, bromine atoms, iodine atoms), alkyl groups (e.g., alkyl groups having 1 to 10 carbon atoms, such as methyl groups, ethyl groups, propyl groups, isopropyl groups, butyl groups, s-butyl groups, tert-butyl groups, pentyl groups, hexyl groups, etc., preferably alkyl groups having 1 to 6 carbon atoms, and more preferably alkyl groups having 1 to 3 carbon atoms), cycloalkyl groups (cyclopentyl groups, cyclohexyl groups, etc.), aryl groups (phenyl groups, alkylphenyl groups (tolyl groups, xylyl groups, etc.)), aralkyl groups (benzyl groups, etc.), alkoxy groups (e.g., methoxy groups, ethoxy groups, etc.), Examples of the alkyl group include an alkoxy group having 1 to 4 carbon atoms, a polyoxyalkylene group (for example, a dioxyethylene group, etc.), a cycloalkoxy group (for example, a cycloalkyloxy group having 5 to 10 carbon atoms, such as a cyclohexyloxy group, etc.), an aryloxy group (for example, a phenoxy group, etc.), an aralkyloxy group (for example, a benzyloxy group, etc.), an alkylthio group (for example, an alkylthio group having 1 to 4 carbon atoms, such as a methylthio group, an ethylthio group, etc.), a cycloalkylthio group (for example, a cyclohexylthio group, etc.), an arylthio group (for example, a thiophenoxy group, etc.), an aralkylthio group (for example, a benzylthio group, etc.), an acyl group (for example, an acetyl group, etc.), a nitro group, and a cyano group. Among these, a halogen atom, an alkyl group, an alkoxy group, and an aryloxy group are preferred, and an alkyl group (for example, a methyl group, an ethyl group, etc.) is particularly preferred.
[0024] In formula (1), n may be, for example, an integer of 1 to 4, preferably an integer of 1 to 3, and more preferably 2.
[0025] Specific examples of hydroxy group-containing (meth)acrylates include 1-hydroxy C1-C8 alkyl (meth)acrylates such as 1-hydroxymethyl (meth)acrylate, 1-hydroxyethyl (meth)acrylate, 1-hydroxyheptyl (meth)acrylate, 1-hydroxybutyl (meth)acrylate, and 1-hydroxypentyl (meth)acrylate; 2-hydroxy C2-C9 alkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 2-hydroxypentyl (meth)acrylate, and 2-hydroxyhexyl (meth)acrylate; 3-hydroxypropyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 3-hydroxybutyl (meth)acrylate; ) acrylate, 3-hydroxypentyl (meth)acrylate, 3-hydroxyhexyl (meth)acrylate, 3-hydroxyheptyl (meth)acrylate, and other 3-hydroxy C3 to C10 alkyl (meth)acrylates; 4-hydroxybutyl (meth)acrylate, 4-hydroxypentyl (meth)acrylate, 4-hydroxyhexyl (meth)acrylate, 4-hydroxyheptyl (meth)acrylate, and other 4-hydroxy C4 to C11 alkyl (meth)acrylates; 2-chloro-2-hydroxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, and other 4-hydroxy C4 to C11 alkyl (meth)acrylates. Among these, from the viewpoint of mechanical strength and heat resistance durability, hydroxy group-containing (meth)acrylates in which n is 2, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 2-hydroxybutyl (meth)acrylate, and hydroxy group-containing (meth)acrylates in which n is 3, such as 3-hydroxypropyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 3-hydroxypentyl (meth)acrylate, are preferred. In particular, hydroxy group-containing (meth)acrylates in which n is 2 are preferred, and among these, 2-hydroxyethyl (meth)acrylate is preferred. The hydroxy group-containing (meth)acrylates may be used alone or in combination of two or more.
[0026] When the (meth)acrylic resin (A) contains a structural unit derived from a hydroxyl group-containing (meth)acrylate, the content of the structural unit derived from a hydroxyl group-containing (meth)acrylate is preferably from 0.3 to 5.5 parts by mass, more preferably from 0.3 to 4 parts by mass, even more preferably from 0.4 to 3 parts by mass, and particularly preferably from 0.5 to 2.5 parts by mass, per 100 parts by mass of all structural units constituting the (meth)acrylic resin (A), from the viewpoint of mechanical strength and heat resistance durability.
[0027] Specific examples of monomers having a carboxy group (hereinafter also referred to as "carboxy group-containing monomers") include (meth)acrylic acid, maleic acid, maleic anhydride, fumaric acid, crotonic acid, and carboxyalkyl (meth)acrylates (e.g., carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate). Among these, acrylic acid is preferred. The monomers having a carboxy group may be used alone or in combination of two or more.
[0028] When the (meth)acrylic resin (A) contains a constituent unit derived from a monomer having a carboxy group, the content of the constituent unit derived from the carboxy group-containing monomer may be 0.05 parts by mass or more and 5.5 parts by mass or less, relative to 100 parts by mass of all constituent units constituting the (meth)acrylic resin (A), and from the viewpoints of mechanical strength and heat resistance durability, it is preferably 0.05 parts by mass or more and 3 parts by mass or less, and more preferably 0.1 parts by mass or more and 2 parts by mass or less.
[0029] The mass ratio of the constituent units derived from the monomer having a carboxy group to the constituent units derived from the hydroxyl group-containing (meth)acrylate is preferably 0.06 or more and 1.0 or less, more preferably 0.06 or more and 0.9 or less, even more preferably 0.08 or more and 0.8 or less, and particularly preferably 0.1 or more and 0.7 or less, from the viewpoints of mechanical strength and heat resistance durability.
[0030] Examples of the monomer having a nitrogen atom include an amino group-containing monomer, an amide group-containing monomer, and other nitrogen atom-containing monomers. The monomer having a nitrogen atom may be used alone or in combination of two or more kinds.
[0031] Examples of the amino group-containing monomer include primary amino group-containing monomers such as aminomethyl (meth)acrylate and aminoethyl (meth)acrylate; secondary amino group-containing monomers such as t-butylaminoethyl (meth)acrylate; and tertiary amino group-containing monomers such as ethylaminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, and diethylaminoethyl (meth)acrylate. From the viewpoint of preventing a decrease in the releasability of the separation film that can be laminated on the adhesive layer, it is preferable that the composition does not substantially contain a structural unit derived from a monomer having an amino group. Note that, "substantially does not contain" means that the composition is less than 1.0 part by mass with respect to 100 parts by mass of all structural units that constitute the (meth)acrylic resin (A).
[0032] Examples of amide group-containing monomers include (meth)acrylamide; alkoxyalkyl (meth)acrylamide-based monomers such as methoxymethyl (meth)acrylamide, ethoxymethyl (meth)acrylamide, propoxymethyl (meth)acrylamide, isopropoxymethyl (meth)acrylamide, n-butoxymethyl (meth)acrylamide, and isobutoxymethyl (meth)acrylamide; hydroxyl group-containing amide monomers such as N-(hydroxymethyl)acrylamide; dialkyl (meth)acrylamide-based monomers such as dimethyl (meth)acrylamide and diethyl (meth)acrylamide; and heterocyclic amide monomers such as (meth)acryloylmorpholine.
[0033] More specifically, for example, N-methylol(meth)acrylamide, N-(2-hydroxyethyl)(meth)acrylamide, N-(3-hydroxypropyl)(meth)acrylamide, N-(4-hydroxybutyl)(meth)acrylamide, N-(5-hydroxypentyl)(meth)acrylamide, N-(6-hydroxyhexyl)(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, Acrylamide, N-(3-dimethylaminopropyl)(meth)acrylamide, N-(1,1-dimethyl-3-oxobutyl)(meth)acrylamide, N-[2-(2-oxo-1-imidazolidinyl)ethyl](meth)acrylamide, 2-(meth)acryloylamino-2-methyl-1-propanesulfonic acid, N-(methoxymethyl)(meth)acrylamide, N-(ethoxymethyl)(meth)acrylamide, N-(propoxymethyl)(meth)acrylamide, N-(1-methyl)(meth)acrylamide, N-(1-methylpropoxymethyl)(meth)acrylamide, N-(2-methylpropoxymethyl)(meth)acrylamide (also known as N-(isobutoxymethyl)(meth)acrylamide), N-(butoxymethyl)(meth)acrylamide, N-(1,1-dimethylethoxymethyl)(meth)acrylamide, N-(2-methoxyethyl)(meth)acrylamide, N-(2-ethoxyethyl)(meth)acrylamide, N-(2 Examples of the acrylamide include N-[2-(1-methylethoxy)ethyl](meth)acrylamide, N-[2-(1-methylpropoxy)ethyl](meth)acrylamide, N-[2-(2-methylpropoxy)ethyl](meth)acrylamide (also known as N-(2-isobutoxyethyl)acrylamide), N-(2-butoxyethyl)(meth)acrylamide, and N-[2-(1,1-dimethylethoxy)ethyl](meth)acrylamide.
[0034] The (meth)acrylic resin (A) may further contain a structural unit derived from a styrene-based monomer, a structural unit derived from a vinyl-based monomer, a structural unit derived from a monomer having multiple (meth)acryloyl groups in the molecule, and the like.
[0035] Examples of styrene-based monomers include styrene; alkyl styrenes such as methylstyrene, dimethylstyrene, trimethylstyrene, ethylstyrene, diethylstyrene, triethylstyrene, propylstyrene, butylstyrene, hexylstyrene, heptylstyrene, and octylstyrene; halogenated styrenes such as fluorostyrene, chlorostyrene, bromostyrene, dibromostyrene, and iodostyrene; nitrostyrene; acetylstyrene; methoxystyrene; and divinylbenzene.
[0036] Examples of vinyl monomers include fatty acid vinyl esters such as vinyl acetate, vinyl propionate, vinyl butyrate, vinyl 2-ethylhexanoate, and vinyl laurate; vinyl halides such as vinyl chloride and vinyl bromide; vinylidene halides such as vinylidene chloride; nitrogen-containing aromatic vinyls such as vinylpyridine, vinylpyrrolidone, and vinylcarbazole; and conjugated diene monomers such as butadiene, isoprene, and chloroprene.
[0037] Examples of monomers having multiple (meth)acryloyl groups in the molecule include monomers having two (meth)acryloyl groups in the molecule, such as 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, and tripropylene glycol di(meth)acrylate; and monomers having three (meth)acryloyl groups in the molecule, such as trimethylolpropane tri(meth)acrylate.
[0038] The weight average molecular weight (Mw) of the (meth)acrylic resin (A) is preferably 1 million to 2 million, more preferably 1.1 million to 1.9 million, even more preferably 1.2 million to 1.8 million, and particularly preferably 1.3 million to 1.7 million, from the viewpoints of mechanical strength and heat resistance. The molecular weight distribution (Mw / Mn) represented by the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the (meth)acrylic resin (A) may be, for example, 1.5 to 10, and is preferably less than 3.5, more preferably 2.5 to 3.5, from the viewpoints of mechanical strength and heat resistance. The weight average molecular weight can be analyzed by gel permeation chromatography (GPC) and is a value calculated in terms of standard polystyrene.
[0039] The (meth)acrylic resin (A) may contain a resin component contained in a high molecular weight region (hereinafter referred to as a "high molecular weight region component") and a resin component contained in a low molecular weight region (hereinafter referred to as a "low molecular weight region component"). As shown in FIG. 2, the high molecular weight region component is a resin component that is contained in a 10% area region (region (1) in FIG. 2) on the high molecular weight side of the peak area derived from the (meth)acrylic resin (A) in a chromatogram obtained by GPC measurement. As shown in FIG. 2, the low molecular weight region component is a component that is contained in a 10% area region (region (2) in FIG. 2) on the low molecular weight side of the peak area derived from the (meth)acrylic resin (A) in a chromatogram obtained by GPC measurement. The GPC measurement is performed according to the method described in the Examples section below.
[0040] The glass transition temperature of the high molecular weight region component may be higher than that of the low molecular weight region component. When the glass transition temperature of the high molecular weight region component is higher than that of the low molecular weight region component, the mechanical strength and heat resistance durability tend to be improved. The glass transition temperatures of the high molecular weight region component and the low molecular weight region component can be adjusted, for example, by selecting the raw materials used in the production of the (meth)acrylic resin (A), adjusting the amount of raw materials to be charged, the order of charging, and the production conditions (for example, temperature, time, nitrogen concentration in the system, etc.).
[0041] The glass transition temperature of the high molecular weight region component is preferably −30° C. or higher, more preferably −28° C. or higher, and further preferably −26° C. or higher, from the viewpoints of mechanical strength and heat resistance durability.
[0042] The glass transition temperature of the low molecular weight region component may be, for example, less than −30° C., and from the viewpoints of mechanical strength and heat resistance durability, is preferably −34° C. or lower, more preferably −36° C. or lower.
[0043] From the viewpoints of mechanical strength and heat resistance and durability, the difference (absolute value) between the glass transition temperature of the high molecular weight region component and the glass transition temperature of the low molecular weight region component is preferably 10° C. or more, more preferably 11° C. or more.
[0044] The glass transition temperature (Tg) of the (meth)acrylic resin (A) is preferably −45° C. or more and −10° C. or less, more preferably −40° C. or more and −15° C. or less, and even more preferably −38° C. or more and −20° C. or less, from the viewpoints of mechanical strength and heat resistance durability.
[0045] The (meth)acrylic resin (A) (or a mixture thereof when two or more types are combined) is dissolved in ethyl acetate and adjusted to a concentration of 20% by mass, and the solution preferably exhibits a viscosity of 20 Pa s or less, and more preferably 0.1 Pa s or more and 7 Pa s or less, at 25° C. The viscosity can be measured by a Brookfield viscometer.
[0046] The (meth)acrylic resin (A) can be produced by known methods such as solution polymerization, bulk polymerization, suspension polymerization, and emulsion polymerization. A polymerization initiator is usually used in the production of the (meth)acrylic resin (A). The polymerization initiator is used in an amount of about 0.001 to 5 parts by mass relative to 100 parts by mass of the total of all monomers used in the production of the (meth)acrylic resin (A). The (meth)acrylic resin (A) may also be produced by a method in which polymerization is promoted by active energy rays such as ultraviolet rays.
[0047] As the polymerization initiator, a thermal polymerization initiator, a photopolymerization initiator, etc. can be used. As the photopolymerization initiator, for example, 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone, etc. can be mentioned. As the thermal polymerization initiator, for example, azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl-2,2'-azobis(2-methylpropionate), and 2,2'-azobis(2-hydroxymethylpropionitrile); lauryl peroxide; Examples of the peroxide include organic peroxides such as diisopropyl peroxydicarbonate, dipropyl peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, and (3,5,5-trimethylhexanoyl)peroxide; and inorganic peroxides such as potassium persulfate, ammonium persulfate, and hydrogen peroxide. Redox initiators using a combination of a peroxide and a reducing agent can also be used as the polymerization initiator.
[0048] As a method for producing the (meth)acrylic resin (A), among the above-mentioned methods, the solution polymerization method is preferred. One example of the solution polymerization method is to mix a monomer and an organic solvent, add a thermal polymerization initiator under a nitrogen atmosphere, and stir for about 3 to 48 hours at about 40 to 90°C, preferably about 50 to 80°C. In order to control the reaction, the monomer and the thermal polymerization initiator may be added continuously or intermittently during polymerization, or may be added in a state dissolved in an organic solvent. As the organic solvent, for example, aromatic hydrocarbons such as toluene and xylene; esters such as ethyl acetate and butyl acetate; aliphatic alcohols such as propyl alcohol and isopropyl alcohol; and ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone can be used.
[0049] (2) Crosslinking agent (B) The pressure-sensitive adhesive composition further contains a crosslinking agent (B). The crosslinking agent (B) can be a compound that reacts with a structural unit derived from a polar functional group-containing monomer in the (meth)acrylic resin (A) and crosslinks the (meth)acrylic resin (A). Specific examples include isocyanate-based compounds, epoxy-based compounds, aziridine-based compounds, and metal chelate-based compounds. Of these, the isocyanate-based compounds, epoxy-based compounds, and aziridine-based compounds are preferably compounds having at least two functional groups in the molecule that can react with the polar functional group in the (meth)acrylic resin. The crosslinking agent (B) may be used alone or in combination of two or more kinds.
[0050] The isocyanate compound is preferably a compound having at least two isocyanato groups (-NCO) in the molecule, and examples thereof include aliphatic isocyanate compounds (e.g., hexamethylene diisocyanate, etc.), alicyclic isocyanate compounds (e.g., isophorone diisocyanate), aromatic isocyanate compounds (e.g., tolylene diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, naphthalene diisocyanate, triphenylmethane triisocyanate, etc.). The crosslinking agent (B) may be an adduct of an isocyanate compound with a polyhydric alcohol compound (e.g., an adduct with glycerol, trimethylolpropane, etc.), an isocyanurate, a biuret-type compound, a urethane prepolymer type isocyanate compound obtained by addition reaction with a polyether polyol, a polyester polyol, an acrylic polyol, a polybutadiene polyol, a polyisoprene polyol, etc. The crosslinking agent (B) may be used alone or in combination of two or more. Among these, representative examples include aromatic isocyanate compounds (e.g., tolylene diisocyanate, xylylene diisocyanate), aliphatic isocyanate compounds (e.g., hexamethylene diisocyanate), or adducts of these with a polyhydric alcohol compound (glycerol, trimethylolpropane). When the crosslinking agent (B) contains an aromatic isocyanate compound and / or an adduct of these with a polyhydric alcohol compound, the mechanical strength and heat resistance tend to be improved.
[0051] The epoxy compound is preferably a compound having at least two epoxy groups in the molecule.Specific examples of the compound include bisphenol A type epoxy resin, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, N,N-diglycidylaniline, N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane, etc. Two or more kinds of epoxy compounds can also be used in combination.
[0052] The aziridine compound is preferably a compound having at least two three-membered ring skeletons, also called ethyleneimine, each consisting of one nitrogen atom and two carbon atoms, in the molecule.Specific examples of the compound include diphenylmethane-4,4'-bis(1-aziridinecarboxamide), toluene-2,4-bis(1-aziridinecarboxamide), triethylenemelamine, isophthaloylbis-1-(2-methylaziridine), tris-1-aziridinylphosphine oxide, hexamethylene-1,6-bis(1-aziridinecarboxamide), trimethylolpropane-tris-β-aziridinylpropionate, and tetramethylolmethane-tris-β-aziridinylpropionate.
[0053] Examples of the metal chelate compound include compounds in which acetylacetone or ethyl acetoacetate is coordinated with a polyvalent metal such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, or zirconium.
[0054] Among these, isocyanate compounds are preferred, and aromatic isocyanate compounds such as tolylene diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, naphthalene diisocyanate, triphenylmethane triisocyanate, and the like, as well as adducts thereof with polyhydric alcohol compounds (e.g., glycerol, trimethylolpropane, etc.).
[0055] The content of the crosslinking agent (B) is preferably from 0.2 to 5.0 parts by mass, more preferably from 0.5 to 2.0 parts by mass, per 100 parts by mass of the solid content of the (meth)acrylic resin (A) (when two or more types are used, the total amount of the (meth)acrylic resins (A)), from the viewpoints of mechanical strength and heat resistance and durability.
[0056] (3) Silane Compounds (C) The pressure-sensitive adhesive composition contains a silane compound (C). By containing the silane compound (C), the adhesiveness (or adhesion) between the pressure-sensitive adhesive layer and a metal layer, a transparent electrode, a glass substrate, etc. can be improved. Examples of the silane compound (C) include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylethoxydimethylsilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-chloropropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 1,3-bis(3'-trimethoxypropyl)urea, 1,6-bis(trimethoxysilyl)hexane, and 1,8-bis(trimethoxysilyl)octane.
[0057] The silane compound may be a silicone oligomer. Specific examples of the silicone oligomer are shown below. In the following specific examples, the silicone oligomer is represented in the form of a combination of monomers.
[0058] Mercaptopropyl group-containing oligomers such as 3-mercaptopropyltrimethoxysilane-tetramethoxysilane oligomer, 3-mercaptopropyltrimethoxysilane-tetraethoxysilane oligomer, 3-mercaptopropyltriethoxysilane-tetramethoxysilane oligomer, and 3-mercaptopropyltriethoxysilane-tetraethoxysilane oligomer.
[0059] Mercaptomethyl group-containing oligomers such as mercaptomethyltrimethoxysilane-tetramethoxysilane oligomer, mercaptomethyltrimethoxysilane-tetraethoxysilane oligomer, mercaptomethyltriethoxysilane-tetramethoxysilane oligomer, and mercaptomethyltriethoxysilane-tetraethoxysilane oligomer.
[0060] Methacryloyloxypropyl group-containing oligomers such as 3-methacryloyloxypropyl trimethoxysilane-tetramethoxysilane oligomer, 3-methacryloyloxypropyl trimethoxysilane-tetraethoxysilane oligomer, 3-methacryloyloxypropyl triethoxysilane-tetramethoxysilane oligomer, 3-methacryloyloxypropyl triethoxysilane-tetraethoxysilane oligomer, 3-methacryloyloxypropyl methyl dimethoxysilane-tetramethoxysilane oligomer, 3-methacryloyloxypropyl methyl dimethoxysilane-tetraethoxysilane oligomer, 3-methacryloyloxypropyl methyl diethoxysilane-tetramethoxysilane oligomer, and 3-methacryloyloxypropyl methyl diethoxysilane-tetraethoxysilane oligomer.
[0061] Acryloyloxypropyl group-containing oligomers such as 3-acryloyloxypropyltrimethoxysilane-tetramethoxysilane oligomer, 3-acryloyloxypropyltrimethoxysilane-tetraethoxysilane oligomer, 3-acryloyloxypropyltriethoxysilane-tetramethoxysilane oligomer, 3-acryloyloxypropyltriethoxysilane-tetraethoxysilane oligomer, 3-acryloyloxypropylmethyldimethoxysilane-tetramethoxysilane oligomer, 3-acryloyloxypropylmethyldimethoxysilane-tetraethoxysilane oligomer, 3-acryloyloxypropylmethyldiethoxysilane-tetramethoxysilane oligomer, and 3-acryloyloxypropylmethyldiethoxysilane-tetraethoxysilane oligomer.
[0062] Vinyl group-containing oligomers such as vinyltrimethoxysilane-tetramethoxysilane oligomer, vinyltrimethoxysilane-tetraethoxysilane oligomer, vinyltriethoxysilane-tetramethoxysilane oligomer, vinyltriethoxysilane-tetraethoxysilane oligomer, vinylmethyldimethoxysilane-tetramethoxysilane oligomer, vinylmethyldimethoxysilane-tetraethoxysilane oligomer, vinylmethyldiethoxysilane-tetramethoxysilane oligomer, and vinylmethyldiethoxysilane-tetraethoxysilane oligomer.
[0063] The silane compound (C) is represented by the following formula (C): [ka] By containing the silane compound (C), the adhesion to metals, transparent electrodes, glass substrates, etc. in high temperature environments is improved, and the heat resistance and durability tend to be excellent. In the above formula (C), R 1 , R 2 and R 3are each independently an alkyl group having 1 to 3 carbon atoms or an alkoxy group having 1 to 3 carbon atoms. Examples of the alkyl group having 1 to 3 carbon atoms include a methyl group, an ethyl group, an n-propyl group, and an i-propyl group, and examples of the alkoxy group having 1 to 3 carbon atoms include a methoxy group, an ethoxy group, an n-propoxy group, and an i-propoxy group.
[0064] In formula (C), L represents an alkylene group having 8 to 12 carbon atoms, or a group in which at least one methylene group constituting the alkylene group is substituted with a group selected from the group consisting of -NH- and O-. Examples of the alkylene group having 8 to 12 carbon atoms include -(CH 2 ) 8 -, -(CH 2 ) 9 -, -(CH 2 ) 10 -, -(CH 2 ) 11 -, -(CH 2 ) 12 - is an example.
[0065] When L is a group in which at least one methylene group constituting an alkylene group having 8 to 12 carbon atoms is substituted with a group selected from the group consisting of -NH- and O-, only one methylene group may be substituted with -NH- or O-, or two or more methylene groups may be substituted with -NH- or O-, respectively. When two or more methylene groups are substituted, typically, the two or more substituted -NH- and / or O- are bonded to an alkylene group having two or more carbon atoms.
[0066] In formula (C), X represents a thiol group (-SH), a cyclic aryl group represented by the following formula: [ka] Epoxy groups, amino groups (-NH 2 ), or an alicyclic epoxy group.
[0067] The alicyclic epoxy group may be one having the following formula: [ka] (In the formula, a represents an integer of 1 to 5.) An example of the monovalent group is a group in which one hydrogen atom has been removed from the structure represented by the following formula:
[0068] Among them, the silane compound (C) is R 1 , R 2 and R 3 are each independently a methoxy group or an ethoxy group, and X is a thiol group, an epoxy group, or an amino group, and is preferably represented by the following formula (C-1): [ka] It is more preferable that the silane compound (C-1) contains or consists of a silane compound (C-1) represented by the following formula (C-1): In the above formula (C-1), m represents an integer of 6 to 10.
[0069] Specific examples of the silane compound (C-1) include 6-glycidoxyhexyltrimethoxysilane, 7-glycidoxyheptyltrimethoxysilane, 8-glycidoxyoctyltrimethoxysilane, 9-glycidoxynonyltrimethoxysilane, and 10-glycidoxydecyltrimethoxysilane. Most of the silane compounds (C-1) are liquid. The silane compound (C-1) may be a commercially available product or may be produced by a known method.
[0070] The content of the silane compound (C) in the pressure-sensitive adhesive composition is usually from 0.01 to 5 parts by mass, and from the viewpoints of mechanical strength and heat resistance durability, it is preferably from 0.1 to 4 parts by mass, and more preferably from 0.2 to 3 parts by mass, relative to 100 parts by mass of the solid content of the (meth)acrylic resin (A) (when two or more types are used, the total of the (meth)acrylic resins (A)).
[0071] (4) Antistatic agent (D) The pressure-sensitive adhesive composition further contains an antistatic agent (D). By containing the antistatic agent (D) in the pressure-sensitive adhesive layer, it is possible to impart antistatic properties to the pressure-sensitive adhesive layer.
[0072] From the viewpoint of further improving the antistatic properties and reworkability, the antistatic agent (D) may be an ionic compound having an inorganic cation or an organic cation and an anion, or may be an ionic compound having an organic cation and an anion.
[0073] Examples of organic cations constituting the ionic compound include imidazolium cation, pyridinium cation, pyrrolidinium cation, ammonium cation, sulfonium cation, phosphonium cation, etc. Specific examples of organic cations include ammonium cations such as tributylmethylammonium cation, trioctylmethylammonium cation, trimethylpropylammonium cation, tetrabutylammonium cation, and (2-hydroxyethyl)trimethylammonium cation; phosphonium cations such as tributyldodecylphosphonium cation; pyridinium cations such as 1-hexylpyridinium cation, 1-octylpyridinium cation, 4-methyl-1-hexylpyridinium cation, 4-methyl-1-octylpyridinium cation, and 4-methyl-1-butylpyridinium cation; pyrrolidinium cations such as butylmethylpyrrolidinium cation and ethylmethylpyrrolidinium cation; and imidazolium cations such as 1-ethyl-3-methylimidazolium cation and 1-butyl-3-methylimidazolium cation.
[0074] As the organic cation, from the viewpoint of further improving antistatic property and reworkability, a nitrogen atom-containing organic cation containing a nitrogen atom is preferred, a cation represented by the following formula (I) is more preferred, an ammonium cation, an imidazolium cation, a pyridinium cation is even more preferred, and an ammonium cation is particularly preferred. Also, as the organic cation, from the viewpoint of suppressing the refractive index fluctuation of the adhesive by using an aromatic ring-containing compound, an aliphatic cation is preferred, and a pyrrolidinium cation or an ammonium cation is more preferred. [ka] [In formula (I), R 5 , R 6 , R 7 and R 8 each independently represents a hydrogen atom, an optionally substituted alkyl group, an optionally substituted alkenyl group, an optionally substituted alkynyl group, an optionally substituted aryl group, or an optionally substituted heterocyclic group; R 5 , R 6 , R 7 and R 8 Adjacent substituents may be bonded together to form a ring.]
[0075] The anion constituting the ionic compound is preferably a fluorine atom-containing anion, and more preferably an anion represented by the following formula (II), from the viewpoint of further improving antistatic properties and reworkability. [Y(SO 2 C q F 2q+1 ) p ] - (II) [In formula (II), Y represents a carbon atom or a nitrogen atom, and when Y is a carbon atom, p is 3, and when Y is a nitrogen atom, p is 2, and q represents an integer of 0 to 10.]
[0076] Specific examples of the anion represented by the above formula (II) include bis(trifluoromethanesulfonyl)imide anion [(CF 3 SO 2 ) 2 N - 〕, bis(pentafluoroethanesulfonyl)imide anion〔(C 2 F 5 SO 2 ) 2 N - 〕, bis(heptafluoropropanesulfonyl)imide anion, bis(nonafluorobutanesulfonyl)imide anion, tris(trifluoromethanesulfonyl)methanide anion [(CF 3 SO 2 ) 3 C - ] etc.
[0077] The anion constituting the ionic compound may be an anion other than the anion represented by the above formula (II), and examples thereof include trifluoromethanesulfonyl(pentafluoroethanesulfonyl)imide anion, trifluoromethanesulfonyl(heptafluoropropanesulfonyl)imide anion, trifluoromethanesulfonyl(nonafluorobutanesulfonyl)imide anion, 1,1,2,2,3,3-hexafluoropropane-1,3-disulfonimide anion, p-toluenesulfonate anion [p-CH 3 C 6 H 4 SO 3 - 〕, dimethylphosphinate anion〔(CH 3 ) 2 POO - 〕, thiocyanate anion [SCN - 〕, carbonate anion [CO 3 2- 〕, tetraarylborate anion (e.g., tetrakis(pentafluorophenyl)borate anion, etc.), dicyanamide anion [(CN) 2 N - ] etc.
[0078] The ionic compounds can be used alone or in combination of two or more. The pressure-sensitive adhesive composition may contain an antistatic agent other than the above-mentioned ionic compounds as the antistatic agent (D).
[0079] The ionic compound is effective in imparting antistatic properties to the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition containing the (meth)acrylic resin (A) and in maintaining various physical properties as a pressure-sensitive adhesive. In particular, when an ionic compound that is solid at room temperature (25°C) is used, the antistatic performance can be maintained for a long period of time compared to when an ionic compound that is liquid at room temperature is used. From the viewpoint of long-term stability of antistatic properties, it is preferable that the ionic compound has a melting point of 23°C or higher. On the other hand, if the melting point is too high, the compatibility with the (meth)acrylic resin (A) becomes poor, so the melting point is preferably 90°C or lower, more preferably 70°C or lower, and even more preferably less than 50°C. The molecular weight of the ionic compound is not particularly limited, but may be, for example, a molecular weight of 700 or lower, or even 500 or lower.
[0080] The content of the antistatic agent (D) in the pressure-sensitive adhesive composition is usually from 0.2 to 8 parts by mass, relative to 100 parts by mass of the solid content of the (meth)acrylic resin (A) (when two or more types are used, the total amount of the (meth)acrylic resins (A)), and from the viewpoints of mechanical strength and heat resistance durability, it is preferably from 0.2 to 5 parts by mass, more preferably from 0.5 to 4 parts by mass.
[0081] (5) Other ingredients The adhesive composition may contain additives such as a crosslinking catalyst, a weathering stabilizer, a tackifier, a plasticizer, a softener, a dye, a pigment, an inorganic filler, light-scattering fine particles, a resin other than the (meth)acrylic resin (A), etc. In addition, it is also useful to blend an ultraviolet-curable compound into the adhesive composition, form an adhesive layer, and then irradiate the adhesive with ultraviolet light to cure the compound, thereby forming a harder adhesive layer.
[0082] When the pressure-sensitive adhesive composition contains a crosslinking catalyst together with the crosslinking agent (B), the pressure-sensitive adhesive layer can be prepared by aging for a short time. In addition, when the crosslinking catalyst is contained, lifting or peeling at the interface between the pressure-sensitive adhesive layer and the adjacent member, foaming of the pressure-sensitive adhesive layer can be more effectively suppressed, and the mechanical strength can be further improved. Examples of the crosslinking catalyst include amine-based compounds such as hexamethylenediamine, ethylenediamine, polyethyleneimine, hexamethylenetetramine, diethylenetriamine, triethylenetetramine, isophoronediamine, trimethylenediamine, polyamino resins, and melamine resins. When an amine-based compound is blended as a crosslinking catalyst in the pressure-sensitive adhesive composition, an isocyanate-based compound is suitable as the crosslinking agent (B).
[0083] The pressure-sensitive adhesive composition can be prepared by mixing the above-mentioned components. The pressure-sensitive adhesive composition may have a gel fraction of, for example, 50% or more and 98% or less, and preferably 60% or more and 95% or less. The gel fraction can be measured, for example, by the following measurement method. The prepared adhesive layer (adhesive sheet) is stored at 23°C and 60% RH for 7 days. After storage, the gel fraction (gel fraction at 23°C (G23)) of the adhesive layer (adhesive sheet) is measured. The gel fraction is measured according to the following [a] to [d]. [a] An adhesive layer having an area of approximately 8 cm x approximately 8 cm is bonded to a metal mesh made of SUS304 having an area of approximately 10 cm x approximately 10 cm (whose mass is Wm). [b] The laminate obtained in [a] above is weighed, and its mass is designated as Ws. Next, the laminate is folded four times so as to encase the adhesive layer and stapled, and then weighed, and its mass is designated as Wb. [c] Place the mesh stapled in [b] above into a glass container, add 60 mL of ethyl acetate to soak it, and then store the glass container at room temperature for 3 days. [d] The mesh is removed from the glass container, dried at 120°C for 4 hours, and then weighed. Its mass is designated as Wa, and the mass is calculated by the following formula: Gel fraction (mass%) = [{Wa-(Wb-Ws)-Wm} / (Ws-Wm)] x 100 The gel fraction is calculated based on the above.
[0084] The adhesive composition is prepared by dissolving or dispersing the above-mentioned components in a solvent, applying the solution or dispersion onto a suitable substrate, and drying the applied solution to form an adhesive layer.
[0085] The thickness of the adhesive layer may be, for example, 10 μm or more and 50 μm or less, and is preferably 15 μm or more and 40 μm or less, more preferably 18 μm or more and 35 μm or less, from the viewpoint of mechanical strength and heat resistance durability. If the thickness of the adhesive layer is 10 μm or more, the adhesiveness can be prevented from decreasing, so that the possibility of a problem occurring in durability can be reduced, and if the thickness is 50 μm or less, the problem of the end face of the adhesive layer adhering to the cutting blade and being removed when cutting the optical laminate can be prevented from occurring.
[0086] <Coat layer 2> The coating layer is a layer disposed between the pressure-sensitive adhesive layer and the first resin film of the polarizing plate, and contains carbon nanotubes (hereinafter, sometimes referred to as "CNTs.") The coating layer is a layer having electrical conductivity (conductive layer) and functions as an antistatic layer.
[0087] The coating layer can be formed, for example, by applying a coating liquid containing carbon nanotubes onto the first resin film and drying the coating liquid. The coating liquid may contain other components such as a surfactant, a binder resin, a crosslinking agent, and a solvent in addition to the carbon nanotubes.
[0088] The solvent is not particularly limited, and examples thereof include water; alcohols such as methanol, ethanol, 2-propanol, and 1-propanol; ethylene glycols such as ethylene glycol, diethylene glycol, trimethylene glycol, triethylene glycol, and tetraethylene glycol; amide compounds such as acetonitrile, N-methylformaldehyde, N,N-dimethylformamide, γ-butyrolactone, and N-methylpyrrolidone; and dimethylsulfoxide. The solvent may be a mixed solvent of water and another solvent. When the coating liquid contains a solvent other than water, the content of the solvent in the coating liquid is preferably 70% by mass or less, and more preferably 0.1 to 50% by mass.
[0089] The crosslinking agent is preferably soluble in the above-mentioned solvent, and more preferably soluble in water. Examples of the crosslinking agent include melamine-based, carbodiimide-based, oxazoline-based, epoxy-based, isocyanate-based, acrylate-based, and alkoxysilane-based compounds, and more specifically, the compounds described in JP-A-2020-175610 and JP-A-2020-175611 are mentioned.
[0090] Examples of the binder resin include epoxy resin, phenol resin, acrylic resin, urethane resin, polyethylene glycol, polyvinyl alcohol, polyvinyl butyral, polyvinyl alcohol-polyethylene copolymer, polyvinyl acetal, polyvinyl alcohol-polyvinyl acetal copolymer, and polyvinyl alcohol-polyvinyl butyral copolymer.
[0091] Examples of surfactants include siloxane-based compounds, fluorine-based compounds, polyether-based compounds, etc., and more specifically, the compounds described in JP-A-2020-175610 and JP-A-2020-175611 can be mentioned.
[0092] The type of carbon nanotube is not particularly limited, and any of single-walled carbon nanotubes, double-walled carbon nanotubes, multi-walled carbon nanotubes, and mixtures containing these in any ratio can be used. From the viewpoint of excellent electrical conductivity, single-walled carbon nanotubes are preferable.
[0093] Commercially available single-walled carbon nanotubes include, for example, the SWeNT series manufactured by Toray Industries, Inc., TUBALL (registered trademark) manufactured by OCSiAl, and the Denatron (registered trademark) Type-C series (CD-100, C-169PF) manufactured by Nagase ChemteX Corporation.
[0094] Commercially available multi-walled carbon nanotubes include, for example, the VGCF (registered trademark) series from Resonac Inc. and Baytubes (registered trademark) from Bayer AG.
[0095] The content of carbon nanotubes in the coating layer is usually from 0.001% by mass to 95% by mass, and may be from 0.005% by mass to 90% by mass, based on the total amount of the coating layer.
[0096] The thickness of the coating layer is usually 1 nm or more and 500 nm or less, and from the viewpoints of antistatic properties and transmittance, is preferably 5 nm or more and 400 nm or less, and more preferably 10 nm or more and 300 nm or less.
[0097] From the viewpoint of antistatic performance, the surface resistance of the coating layer is 1.0×10 12 It is preferable that the resistance is Ω / □ or less, and 1.0×10 11 It is more preferable that the resistance is 1.0×10 10 More preferably, it is 1.0×10 9 It is particularly preferable that the surface resistance of the coating layer is 1.0×10 3 It is preferable that the resistance is Ω / □ or more, and 1.0×10 4 More preferably, it is 1.0×10 5It is more preferable that the surface resistance is Ω / □ or more. The surface resistance of the coating layer can be measured by the method described in the examples.
[0098] <Polarizing plate 20> The polarizing plate has a structure in which a first protective layer is provided on one surface of a polarizer via a first bonding layer, and a second protective layer is provided on the other surface via a second bonding layer. The polarizing plate may be a linear polarizing plate or a composite polarizing plate including a retardation layer. The polarizing plate shown in FIG. 1 is a composite polarizing plate including a retardation layer. Each layer constituting the polarizing plate will be described below.
[0099] <Polarizer 7> The polarizer includes a linearly polarizing layer. The linearly polarizing layer has a property of transmitting linearly polarized light having a vibration plane perpendicular to the absorption axis when unpolarized light is incident on the linearly polarizing layer. The linearly polarizing layer may be a polyvinyl alcohol-based resin film (hereinafter, sometimes referred to as a "PVA-based film") in which iodine is adsorbed and aligned.
[0100] The linear polarizing layer, which is a PVA-based film, may be, for example, a PVA-based film such as a polyvinyl alcohol film, a partially formalized polyvinyl alcohol film, or an ethylene-vinyl acetate copolymer-based partially saponified film, which has been dyed with iodine and stretched. If necessary, the PVA-based film in which iodine has been adsorbed and oriented by the dyeing process may be treated with an aqueous boric acid solution, and then a washing process may be performed to wash off the aqueous boric acid solution. A known method may be used for each step.
[0101] Polyvinyl alcohol resins (hereinafter sometimes referred to as "PVA resins") can be produced by saponifying polyvinyl acetate resins. Polyvinyl acetate resins can be polyvinyl acetate, which is a homopolymer of vinyl acetate, or a copolymer of vinyl acetate and other monomers copolymerizable with vinyl acetate. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and acrylamides having an ammonium group.
[0102] The saponification degree of the PVA resin is usually about 85 to 100 mol%, preferably 98 mol% or more. The PVA resin may be modified, and for example, polyvinyl formal or polyvinyl acetal modified with aldehydes can be used. The average polymerization degree of the PVA resin is usually about 1,000 to 10,000, preferably about 1,500 to 5,000. The saponification degree and average polymerization degree of the PVA resin can be determined in accordance with JIS K 6726 (1994). If the average polymerization degree is less than 1,000, it is difficult to obtain a preferable polarizing performance, and if it exceeds 10,000, the film processability may be poor.
[0103] The method for producing the linearly polarizing layer, which is a PVA-based film, may include the steps of preparing a substrate film, applying a solution of a resin such as a PVA-based resin onto the substrate film, and performing drying to remove the solvent to form a resin layer on the substrate film. A primer layer may be formed in advance on the surface of the substrate film on which the resin layer is to be formed. As the substrate film, a film using a resin material described as a thermoplastic resin used to form a protective film as a protective layer, which will be described later, may be used. As the material for the primer layer, a resin obtained by crosslinking a hydrophilic resin used in the linearly polarizing layer may be mentioned.
[0104] Next, the amount of solvent such as water in the resin layer is adjusted as necessary, and then the base film and the resin layer are uniaxially stretched, and then the resin layer is dyed with iodine to adsorb and align iodine in the resin layer. Next, if necessary, the resin layer with iodine adsorbed and oriented is treated with an aqueous boric acid solution, and then a washing step is performed to wash off the aqueous boric acid solution. This produces a resin layer with iodine adsorbed and oriented, that is, a PVA-based film that becomes a linearly polarizing layer. A known method can be used for each step.
[0105] The amount of boric acid in the boric acid-containing aqueous solution for treating the PVA-based film or resin layer in which iodine is adsorbed and oriented is usually about 2 to 15 parts by mass, preferably 5 to 12 parts by mass, per 100 parts by mass of water. This boric acid-containing aqueous solution preferably contains potassium iodide. The amount of potassium iodide in the boric acid-containing aqueous solution is usually about 0.1 to 15 parts by mass, preferably about 5 to 12 parts by mass, per 100 parts by mass of water. The immersion time in the boric acid-containing aqueous solution is usually about 60 to 1,200 seconds, preferably about 150 to 600 seconds, more preferably about 200 to 400 seconds. The temperature of the boric acid-containing aqueous solution is usually 50°C or higher, preferably 50 to 85°C, more preferably 60 to 80°C.
[0106] The uniaxial stretching of the PVA-based film, the substrate film, and the resin layer may be performed before dyeing, during dyeing, or during boric acid treatment after dyeing, and uniaxial stretching may be performed at each of these multiple stages. The PVA-based film, the substrate film, and the resin layer may be uniaxially stretched in the MD direction (film transport direction). In this case, they may be uniaxially stretched between rolls with different peripheral speeds, or may be uniaxially stretched using a heated roll. The PVA-based film, the substrate film, and the resin layer may be uniaxially stretched in the TD direction (direction perpendicular to the film transport direction). In this case, a so-called tenter method can be used. The above stretching may be dry stretching in which stretching is performed in the atmosphere, or wet stretching in which stretching is performed in a state in which the PVA-based film or the resin layer is swollen with a solvent. In order to exhibit the performance of the linearly polarizing layer, the stretching ratio is 4 times or more, preferably 5 times or more, and particularly preferably 5.5 times or more. There is no particular upper limit to the stretching ratio, but it is preferably 8 times or less from the viewpoint of suppressing breakage and the like.
[0107] The linear polarizing layer produced by the manufacturing method using the substrate film can be obtained by laminating a protective layer and then peeling off the substrate film. This method makes it possible to further reduce the thickness of the linear polarizing layer.
[0108] The thickness of the linearly polarizing layer, which is a PVA-based film, is preferably 1 μm or more, may be 2 μm or more, or may be 5 μm or more, and is preferably 30 μm or less, more preferably 15 μm or less, may be 10 μm or less, or may be 8 μm or less. If the linearly polarizing layer is less than 1 μm thick, defects such as breakage may occur during the process, and if it exceeds 30 μm, the optical film becomes too thick, which is inappropriate.
[0109] <First Protective Layer 10 and Second Protective Layer 9> (First resin film 4 and second resin film 9) As the protective layer, for example, a protective film (first resin film and second resin film) formed from a thermoplastic resin excellent in transparency, mechanical strength, thermal stability, moisture blocking property, isotropy, stretchability, etc. is used. The protective film is preferably laminated on the linear polarizing layer via an attachment layer.
[0110] Specific examples of thermoplastic resins for forming the protective film (first resin film and second resin film) include cellulose resins such as triacetyl cellulose; polyester resins such as polyethylene terephthalate and polyethylene naphthalate; polyethersulfone resins; polysulfone resins; polycarbonate resins; polyamide resins such as nylon and aromatic polyamide; polyimide resins; polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymers; cyclic polyolefin resins having cyclo- and norbornene structures (also called norbornene resins); (meth)acrylic resins; polyarylate resins; polystyrene resins; polyvinyl alcohol resins, and mixtures thereof. The thickness of the protective film is preferably thin from the viewpoint of optical properties, but if it is too thin, the strength decreases and the processability is poor. The appropriate thickness of the protective film is 5 μm or more and 100 μm or less, preferably 10 μm or more and 80 μm or less, and more preferably 15 μm or more and 70 μm or less.
[0111] The protective layer may have anti-reflection properties, anti-glare properties, hard coat properties, etc. (Hereinafter, a protective layer having such properties may be referred to as a "functional protective layer.") When the protective layer is not a functional protective layer, a surface functional layer such as an anti-reflection layer, an anti-glare layer, a hard coat layer, etc. may be provided on one side of the linear polarizing plate. The surface functional layer is preferably provided so as to be in direct contact with the protective layer. The surface functional layer is preferably provided on the side of the protective layer opposite to the linear polarizing layer side.
[0112] The first protective layer provided on the pressure-sensitive adhesive layer side of the polarizer may be a laminate of a retardation layer, a first resin film, and a hard coat layer.
[0113] (Retardation layer 5) The retardation layer is an optical element that exhibits retardation in the in-plane or thickness direction, and includes at least one retardation film. The retardation film may be one, or two or more may be bonded together with a known adhesive or pressure-sensitive adhesive. The retardation film is a film that exhibits retardation in the in-plane or thickness direction, and may be a stretched film or may include a layer of a cured product of a polymerizable liquid crystal compound.
[0114] When the retardation film is a stretched film, the stretched film may be a conventionally known one, and may be a resin film that is uniaxially or biaxially stretched to give a retardation. As the resin film, cellulose films such as triacetyl cellulose and diacetyl cellulose, polyester films such as polyethylene terephthalate, polyethylene isophthalate and polybutylene terephthalate, acrylic resin films such as polymethyl (meth) acrylate and polyethyl (meth) acrylate, polycarbonate films, polyethersulfone films, polysulfone films, polyimide films, polyolefin films, polynorbornene films, etc. may be used, but are not limited thereto.
[0115] When the retardation film includes the above-mentioned cured product layer, the polymerizable liquid crystal compound may be a known polymerizable liquid crystal compound. The polymerizable liquid crystal compound is a compound having at least one polymerizable group and having liquid crystal properties.
[0116] The polymerizable group of the polymerizable liquid crystal compound means a group involved in a polymerization reaction, and is preferably a photopolymerizable group. The photopolymerizable group means a group that can be involved in a polymerization reaction by an active radical or an acid generated from a photopolymerization initiator. Examples of the polymerizable group include a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, a (meth)acryloyloxy group, an oxiranyl group, an oxetanyl group, a styryl group, and an allyl group. Among them, a (meth)acryloyloxy group, a vinyloxy group, an oxiranyl group, and an oxetanyl group are preferred, and an acryloyloxy group is more preferred. The liquid crystal property of the polymerizable liquid crystal compound may be a thermotropic liquid crystal or a lyotropic liquid crystal, and when the thermotropic liquid crystal is classified by the degree of order, it may be a nematic liquid crystal or a smectic liquid crystal. When two or more types of polymerizable liquid crystal compounds are used in combination to form a cured layer of the polymerizable liquid crystal compound, it is preferable that at least one type has two or more polymerizable groups in the molecule.
[0117] When the retardation film includes the cured product layer, the retardation film may include an alignment film. The alignment film has an alignment regulating force for aligning the polymerizable liquid crystal compound in a desired direction. The alignment film may be a vertical alignment film in which the molecular axis of the polymerizable liquid crystal compound is aligned vertically to the planar direction of the optical laminate, a horizontal alignment film in which the molecular axis of the polymerizable liquid crystal compound is aligned horizontally to the planar direction of the optical laminate, or an inclined alignment film in which the molecular axis of the polymerizable liquid crystal compound is aligned at an angle to the planar direction of the optical laminate.
[0118] The cured product layer can be formed by applying a composition for forming a retardation film containing a polymerizable liquid crystal compound, a solvent, and various additives as necessary, on an alignment film to form a coating film, and solidifying (curing) the coating film. Alternatively, the composition can be applied to a substrate film to form a coating film, and the coating film can be stretched together with the substrate film to form a cured product layer. The composition may contain a polymerization initiator, a reactive additive, a leveling agent, a polymerization inhibitor, and the like, in addition to the polymerizable liquid crystal compound and solvent described above. The polymerizable liquid crystal compound, the solvent, the polymerization initiator, the reactive additive, the leveling agent, the polymerization inhibitor, and the like can be appropriately used as known polymerizable liquid crystal compounds, solvents, polymerization initiators, reactive additives, leveling agents, polymerization inhibitors, and the like. As the substrate film, a film using a resin material described as the thermoplastic resin used to form the protective film as the protective layer can be used.
[0119] (Hard Coat Layer 3) The hard coat layer is a layer provided to improve the hardness and scratch resistance of the first protective layer, etc. The hard coat layer is, for example, a cured layer of a photocurable composition (composition for forming a hard coat layer) containing a photocurable resin and a photopolymerization initiator.
[0120] Examples of photocurable resins include acrylic resins, silicone resins, polyester resins, urethane resins, amide resins, and epoxy resins.
[0121] When the hard coat layer forming composition is a radical curable composition, a radical polymerization initiator can be used as the photopolymerization initiator. Examples of the radical polymerization initiator include α-hydroxyacetophenone-based photopolymerization initiators, α-aminoacetophenone-based photopolymerization initiators, acylphosphine oxide-based photopolymerization initiators, and intramolecular hydrogen abstraction photopolymerization initiators. Among them, from the viewpoint of easily shortening the curing time of the hard coat layer forming composition, α-hydroxyacetophenone-based photopolymerization initiators and α-aminoacetophenone-based photopolymerization initiators are preferred.
[0122] The hard coat layer may contain additives to improve its strength. The additives are not limited, and examples thereof include inorganic fine particles, organic fine particles, and mixtures thereof.
[0123] The thickness of the hard coat layer may be, for example, from 0.1 μm to 10 μm, and preferably from 0.5 μm to 5 μm.
[0124] <First bonding layer 6 and second bonding layer 8> The polarizer and the first and second protective layers may be attached to each other by an attachment layer. The attachment layer is a pressure-sensitive adhesive layer or an adhesive layer. When the attachment layer is a pressure-sensitive adhesive layer, it can be formed using a known pressure-sensitive adhesive composition. In addition, the pressure-sensitive adhesive composition for forming the pressure-sensitive adhesive layer 1 described above may be used as the pressure-sensitive adhesive composition.
[0125] When the attachment layer is an adhesive layer, the adhesive layer can be formed by curing a curable component in an adhesive composition. The adhesive composition for forming the adhesive layer is an adhesive other than a pressure-sensitive adhesive (adhesive), and examples thereof include a water-based adhesive and an active energy ray curable adhesive.
[0126] Examples of the water-based adhesive include an adhesive in which a polyvinyl alcohol resin is dissolved or dispersed in water. The drying method when using a water-based adhesive is not particularly limited, but for example, a method of drying using a hot air dryer or an infrared dryer can be adopted.
[0127] Examples of the active energy ray curable adhesive include a solventless active energy ray curable adhesive containing a curable compound that is cured by irradiation with active energy rays such as ultraviolet rays, visible light, electron beams, and X-rays. By using a solventless active energy ray curable adhesive, the adhesion between layers can be improved.
[0128] <Separate film> The optical laminate may have a separate film attached to the surface of the pressure-sensitive adhesive layer, and the surface of the pressure-sensitive adhesive layer may be protected until use. The optical laminate provided with the separate film in this way may be produced, for example, by applying the above-mentioned pressure-sensitive adhesive composition onto the separate film to form a pressure-sensitive adhesive layer, and further laminating a polarizing plate on the obtained pressure-sensitive adhesive layer, applying the pressure-sensitive adhesive composition onto the polarizing plate to form a pressure-sensitive adhesive layer, and laminating a separate film on the pressure-sensitive adhesive surface to protect it, applying the above-mentioned pressure-sensitive adhesive composition onto the separate film to form a pressure-sensitive adhesive layer, laminating another separate film on the obtained pressure-sensitive adhesive layer, peeling off one of the separate films, and laminating a polarizing plate on the exposed pressure-sensitive adhesive surface. In particular, the method of applying the above-mentioned pressure-sensitive adhesive composition onto the separate film to form a pressure-sensitive adhesive layer, laminating another separate film on the obtained pressure-sensitive adhesive layer, peeling off one of the separate films, and laminating a polarizing plate on the exposed pressure-sensitive adhesive surface is preferred from the viewpoint of stabilizing the physical properties during the curing period of the pressure-sensitive adhesive. The separate film may be, for example, a film made of various resins such as polyethylene terephthalate, polybutylene terephthalate, polycarbonate, polyarylate, etc., used as a base material, and a release treatment such as silicone treatment may be applied to the bonding surface of this base material with the pressure-sensitive adhesive layer.
[0129] The optical layered body of the present invention can suppress a gradual increase in adhesion to a substrate due to heat and has good reworkability, and therefore can be suitably used for applications in which the layered body is attached to a substrate such as glass in an image display device or the like.
[0130] [Image display device] The image display device according to the present invention includes the optical laminate according to the present invention. The image display device includes, for example, a glass substrate and the optical laminate bonded to the glass substrate. A metal layer such as metal wiring may be provided on a part of the surface of the glass substrate facing the optical laminate. The metal layer may be a transparent electrode layer made of a metal oxide such as ITO.
[0131] In the manufacture of an image display device, if any defect occurs after the optical laminate is attached to a glass substrate, a so-called reworking operation may be required, in which the optical laminate is peeled off from the glass substrate and another optical laminate is attached to the glass substrate. Here, it may take a long time from attachment of the optical laminate to the glass substrate until it is peeled off, or the image display device may be exposed to the elements. However, the optical laminate according to the present invention can reduce the increase in adhesion to the substrate due to heat and has good reworkability, so that the optical laminate can be easily peeled off from the glass substrate and the adhesive can be prevented from remaining on the surface of the glass substrate after peeling.
[0132] Although the preferred embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment. For example, the optical laminate may not have a hard coat layer between the coating layer and the first resin film, and the coating layer and the first resin film may be in direct contact with each other. In addition, the optical laminate may not have a second protective layer. In addition, the optical laminate may not have a retardation layer, and the polarizing plate may be a linear polarizing plate.
[0133] In addition, although the optical laminate 100 including the polarizing plate 20 has been described in FIG. 1, the optical laminate may be a laminate including an optical film having other optical functions as long as it includes a resin film, a coating layer, and a pressure-sensitive adhesive layer in this order. For example, the optical laminate may include a retardation plate having a protective layer on one or both sides of a retarder, a reflective film, a semi-transmissive reflective film, a brightness enhancing film, a film with an anti-glare function, or the like, instead of the polarizing plate 20 in FIG. 1. In addition, these optical films may be used alone or in combination of two or more kinds. EXAMPLES
[0134] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. In the following, "parts" and "%" representing the amount used or the content are based on mass unless otherwise specified.
[0135] <Production Example 1> A mixed solution of 86.4 parts of ethyl acetate, 68.7 parts of butyl acrylate, 20 parts of methyl acrylate, 10 parts of methyl methacrylate, 1.0 parts of 2-hydroxyethyl acrylate, and 0.3 parts of acrylic acid was charged into a reaction vessel equipped with a cooling tube, a nitrogen introduction tube, a thermometer, and a stirrer, and the air in the apparatus was replaced with nitrogen gas to make it oxygen-free, while the internal temperature was raised to 60°C. Then, a solution of 0.10 parts of azobisisobutyronitrile (polymerization initiator) dissolved in 13.7 parts of ethyl acetate was added in its entirety. After the addition of the polymerization initiator, the temperature was maintained at 60°C for 4 hours. Then, ethyl acetate was added to adjust the concentration of the (meth)acrylic resin to 20% by mass, and an ethyl acetate solution of the (meth)acrylic resin was prepared.
[0136] The weight average molecular weight (Mw) and number average molecular weight (Mn) of the obtained (meth)acrylic resin were measured. Mw and Mn were measured in terms of standard polystyrene using a GPC apparatus with three columns in series, one "TSKgel guardcolumn HHR-H(S)" manufactured by Tosoh Corporation and two "TSKgel GMHHR-H", and tetrahydrofuran as the eluent under the conditions of a sample concentration of 2 mg / mL, a sample introduction amount of 100 μL, a temperature of 40° C., and a flow rate of 1 mL / min.
[0137] The obtained (meth)acrylic resin was subjected to molecular weight fractionation into high molecular weight region components and low molecular weight region components. As the high molecular weight region components, components in the region of 10% of the high molecular weight side of the peak derived from the (meth)acrylic resin in the chromatogram obtained by GPC measurement were fractionated, and as the low molecular weight region components, components in the region of 10% of the low molecular weight side of the peak derived from the (meth)acrylic resin in the chromatogram obtained by GPC measurement were fractionated. As columns, one "TSKgel guardcolumnHHR-H(S)" manufactured by Tosoh Corporation and two "TSKgel GMHHR-H" were connected in series in a GPC device (LaboACE LC-7080 manufactured by Japan Analytical Industry Co., Ltd.), and molecular weight fractionation was performed using tetrahydrofuran as an eluent under the conditions of a sample concentration of 2.5 mg / mL, a sample introduction amount of 2 mL, room temperature, and a flow rate of 6 mL / min.
[0138] After molecular weight fractionation of the obtained (meth)acrylic resin, the glass transition temperature (Tg) of the high molecular weight region component and the low molecular weight region component was measured. Tg was measured using a differential scanning calorimeter (DSC) "EXSTAR DSC6000" manufactured by SII Nano Technology Co., Ltd. under conditions of a nitrogen atmosphere, a measurement temperature range of -80 to 50°C, and a heating rate of 10°C / min. The monomer composition of the monomer mixture used, the Mw and molecular weight distribution (Mw / Mn) of the obtained (meth)acrylic resin, and Tg are summarized in Table 1.
[0139] [Table 1]
[0140] The abbreviations in the "Monomer composition" column of Table 1 represent the following monomers. BA: Butyl acrylate MA: Methyl acrylate MMA: Methyl methacrylate HEA: 2-hydroxyethyl acrylate AA: Acrylic acid
[0141] A crosslinking agent, a silane compound and an antistatic agent (ionic compound) were mixed in the amounts (parts by mass) shown in Table 2 relative to 100 parts by mass of the solid content of the solution into an ethyl acetate solution of the (meth)acrylic resin (resin concentration: 20%), and ethyl acetate was further added so that the solid content concentration became 14% by mass to prepare a pressure-sensitive adhesive composition 1. In Table 2, the blending amounts (parts by mass) of the (meth)acrylic resin, the crosslinking agent, the silane compound and the ionic compound are calculated as solid contents.
[0142] <Production Example 2> As shown in Table 2, pressure-sensitive adhesive composition 2 was prepared in the same manner as pressure-sensitive adhesive composition 1, except that no ionic compound was added.
[0143] [Table 2]
[0144] The "type" of each component in Table 2 refers to the following materials. (Crosslinking agent) B: D-103 (trade name, ethyl acetate solution of trimethylolpropane adduct of tolylene diisocyanate, manufactured by Mitsui Chemicals, Inc., solid content concentration 75% by mass) (Silane compounds) C: KBM-4803 (product name, 8-glycidoxyoctyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.) (ionic compounds) D: Methyltributylammonium bis(trifluoromethylsulfonyl)imide
[0145] <Production Example 3> The components shown in Table 3 were mixed and stirred in the amounts (parts by mass) shown in Table 3 to obtain a composition for forming a hard coat layer HC-1. [Table 3]
[0146] As the components in Table 3, the following materials were used. Photocurable resin: Beamset 710 (product name, pentaerythritol polyacrylate, manufactured by Arakawa Chemical Industries, Ltd.) Photoinitiator A: Omnirad2959 (trade name, manufactured by IGM Resins) Solvent: Methyl ethyl ketone
[0147] <Production Example 4> 50 g of modified polyvinyl alcohol resin containing acetoacetyl groups (manufactured by Mitsubishi Chemical Corporation, product name: Gohsenex Z-410) was dissolved in 950 g of pure water, heated at 90°C for 2 hours, and then cooled to room temperature to obtain a PVA solution. This PVA solution, pure water, maleic acid, glyoxal, and urea were mixed so that the concentration of the polyvinyl alcohol resin was 3.0% by mass, the concentration of maleic acid was 0.01% by mass, the concentration of glyoxal was 0.15% by mass, and the concentration of urea was 0.1% by mass to obtain a water-based adhesive.
[0148] [Example 1] <Preparation of retardation layer with substrate layer> An alignment film (thickness 40 nm) and a liquid crystal cured film (thickness 0.5 μm) (collectively referred to as "retardation layer") were formed on a transparent film substrate (polyolefin resin film, thickness 24 μm) as a substrate layer (resin film) by the method described in
[0261] to
[0266] of JP2016-027431A, to obtain a retardation layer with a substrate layer.
[0149] <Formation of hard coat layer> The composition for forming a hard coat layer HC-1 prepared in Production Example 3 was applied by bar coating to the substrate layer side surface of the retardation layer with substrate layer prepared above so that the film thickness after drying would be about 1 μm. The coating film was dried in an oven at 60° C. for 150 seconds, and then exposed to an electrodeless lamp H bulb manufactured by Fusion UV Systems Co., Ltd. with an illuminance of 400 mW / cm. 2 , light intensity 300mJ / cm 2 The coating film was irradiated with ultraviolet light of 1000 nm to form a hard coat layer.
[0150] <Preparation of polarizer> A 30 μm thick polyvinyl alcohol (PVA) resin film was immersed in pure water at a temperature of 21.5° C. for 80 seconds (swelling treatment), and then immersed in an aqueous solution at a temperature of 23° C. containing 1.0 mM iodine with a mass ratio of potassium iodide / boric acid / water of 2 / 2 / 100 for 55 seconds (dyeing process). Then, it was immersed in an aqueous solution at a temperature of 63° C. with a mass ratio of potassium iodide / boric acid / water of 2.5 / 4 / 100 for 76 seconds (first crosslinking process). Then, it was immersed in an aqueous solution at a temperature of 45° C. with a mass ratio of potassium iodide / boric acid / zinc chloride / water of 3 / 5.5 / 0.6 / 100 for 10 seconds (second crosslinking process, metal ion treatment process). Then, it was immersed in a washing bath for washing (washing process), and dried at a temperature of 38° C. (drying process), to obtain a polarizer with a thickness of 12 μm in which iodine was adsorbed and aligned on the PVA resin film. The stretching was mainly carried out in the dyeing step and the first crosslinking step, and the total stretching ratio was 5.85 times.
[0151] <Preparation of polarizing plate> A retardation layer with a base layer on which a hard coat layer was formed as described above was prepared as protective layer (1), and a triacetyl cellulose film (manufactured by Fujifilm Corporation, product name "TJ40UL", thickness: 40 μm) was prepared as protective layer (2). Two types of protective layers (1) and (2) were produced by subjecting protective layer (2) to a saponification treatment.
[0152] The two types of protective layers (1) and (2) prepared above were laminated to each surface of the polarizer prepared above using a roll laminator via the aqueous adhesive prepared in Production Example 4, and then dried at a temperature of 80°C for 5 minutes to obtain a polarizing plate (layer structure: protective layer (2) / adhesive layer / polarizer / adhesive layer / protective layer (1)). Here, the protective layer (1) was laminated so that its retardation layer surface faced the polarizer. The aqueous adhesive interposed between the polarizer and the protective layers (1) and (2) was adjusted so that the thickness of the adhesive layer after drying was 100 nm on both sides.
[0153] <Preparation of Coating Layer (Conductive Layer)> A CNT-based conductive coating agent (manufactured by Nagase ChemteX Corporation, product name "Denatron C-169PF-A") and a crosslinking agent for CNT-based conductive coating agents (manufactured by Nagase ChemteX Corporation, product name "Denatron C-169PF-B") were mixed in a ratio (mass ratio) of Denatron C-169PF-A:C-169PF-B = 3:2, and stirred for 10 minutes to prepare a coating solution for forming a coating layer with a concentration of 1.5%. The hard coat layer surface of the protective layer (1) of the polarizing plate prepared above was subjected to a corona treatment (4.0 KJ / m 2 ) was applied to the substrate, the coating liquid prepared above was applied thereto, and the substrate was dried by heating at 100° C. for 3 minutes to form a coating layer (conductive layer) having a thickness of 50 nm. This resulted in a polarizing plate with a coating layer.
[0154] <Preparation of Polarizing Plate with Pressure-Sensitive Adhesive Layer> The adhesive composition prepared in Production Example 1 above was applied to the release-treated surface of a separate film (manufactured by Mitsubishi Chemical Corporation, product name "Diafoil MRV38 (V04)") made of a release-treated polyethylene terephthalate film using an applicator so that the thickness after drying would be 25 μm, and dried at 100° C. for 1 minute to prepare an adhesive layer (adhesive sheet). The surface (adhesive layer surface) of the adhesive layer prepared above opposite to the separate film was attached to the coating layer surface of the coating layer-attached polarizing plate prepared above using a laminator, and then aged for 7 days under conditions of a temperature of 23° C. and a relative humidity of 60%, to obtain an adhesive layer-attached polarizing plate.
[0155] [Example 2] A pressure-sensitive adhesive layer-attached polarizing plate was produced in the same manner as in Example 1, except that the concentration of the coating liquid for forming the coat layer was 0.15% and the thickness after drying was 5 nm.
[0156] [Comparative Examples 1 to 2] A pressure-sensitive adhesive layer-attached polarizing plate was produced in the same manner as in Example 1, except that the structures shown in Table 4 were used for producing the pressure-sensitive adhesive layer and the coating layer in Example 1.
[0157] [Measurement of adhesion to substrate after heat / humid heat treatment] The polarizing plate with the adhesive layer obtained in the examples and comparative examples was cut to a width of 25 mm to prepare a test piece. The separate film was peeled off from the test piece, and the adhesive layer surface of the test piece was attached to a glass substrate (alkali-free glass) using a laminator device (manufactured by Fujipla Co., Ltd., product name "LPC1506") under normal temperature and normal humidity environment (23°C, 50% RH). After initial (0 hours) and after 24 hours of heat treatment at 50°C or 24 hours of moist heat treatment at 65°C, 93% RH, the end of the test piece was pulled at an angle of 180°C under normal temperature and normal humidity environment at a speed of 300 mm / min, and the adhesion force when peeled off from the glass substrate was measured. The measurement was performed using a Tensilon universal testing machine (product name "STB-1110-HS10") manufactured by A&D Co., Ltd. The results are shown in Table 4. It can be said that the lower the adhesion force to the substrate after heat treatment and moist heat treatment, the better the reworkability. In addition, in both the examples and the comparative examples, no adhesive remained on the glass substrate surface after peeling.
[0158] [Measurement of charged voltage immediately after peeling off the separation film] The polarizing plate with adhesive layer obtained in the examples and comparative examples was cut into 20 cm square to prepare a test piece. The protective layer (2) side of the test piece was attached to a glass substrate (alkali-free glass) with adhesive tape, and the adhesive layer of the polarizing plate was grounded. The end of the separate film was pulled at an angle of 180° and a speed of 30 m / min under normal temperature and humidity environment (23°C, 50% RH), and the charged voltage when peeled off from the adhesive layer was measured. The charged voltage was measured using a static electricity meter (product name "SK-035 / 200") manufactured by Keyence Corporation. The results are shown in Table 4.
[0159] [Measurement of surface resistance of coating layer] Using Mitsubishi Chemical Corporation's Hiresta UP (product name "MCP-HT450"), the surface resistance of the coating layer of the polarizing plates with a coating layer obtained in the Examples and Comparative Examples was measured at an applied voltage of 10 V. The results are shown in Table 4.
[0160] [Table 4] [Explanation of symbols]
[0161] 1...adhesive layer, 2...coating layer, 3...hard coating layer, 4...first resin film, 5...retardation layer, 6...first bonding layer, 7...polarizer, 8...second bonding layer, 9...second resin film (second protective layer), 10...first protective layer, 20...polarizing plate, 100...optical laminate.
Claims
1. The film has a resin film, a coating layer, and a pressure-sensitive adhesive layer in this order, The coating layer contains carbon nanotubes, The pressure-sensitive adhesive layer comprises a (meth)acrylic resin (A), a crosslinking agent (B), a silane compound (C), and an antistatic agent (D).
2. The optical laminate according to claim 1 , wherein the antistatic agent (D) is an ionic compound comprising a nitrogen-containing organic cation and an anion.
3. The optical laminate according to claim 2, wherein the nitrogen atom-containing organic cation is a cation represented by the following formula (I): 【Chemistry 1】 [In formula (I), R 5 , R 6 , R 7 and R 8 each independently represents a hydrogen atom, an optionally substituted alkyl group, an optionally substituted alkenyl group, an optionally substituted alkynyl group, an optionally substituted aryl group, or an optionally substituted heterocyclic group; R 5 , R 6 , R 7 and R 8 Adjacent substituents may be bonded together to form a ring.
4. The optical laminate according to claim 2 , wherein the anion is a fluorine atom-containing anion.
5. The optical laminate according to claim 4 , wherein the fluorine atom-containing anion is an anion represented by the following formula (II): [Y(SO 2 C q F 2q+1 ) p - (II) [In formula (II), Y represents a carbon atom or a nitrogen atom, when Y is a carbon atom, p is 3, and when Y is a nitrogen atom, p is 2, and q represents an integer of 0 to 10.]
6. The optical laminate according to claim 2, wherein the anion is at least one selected from the group consisting of p-toluenesulfonate anion, dimethylphosphinate anion, thiocyanate anion, carbonate anion, tetraarylborate anion, and dicyanamide anion.
7. The optical laminate according to claim 1 , further comprising a hard coat layer between the resin film and the coating layer.
8. The optical laminate according to claim 1 , further comprising a polarizer on the opposite side of the resin film to the coating layer.
9. The optical laminate according to claim 8 , further comprising a second resin film on the opposite side of the polarizer to the resin film.
10. An image display device comprising the optical laminate according to any one of claims 1 to 9.
Citation Information
Patent Citations
Polarizing plate
JP1994313807A